A model of managing knowledge for software maintenance as a service (SMaaS) in a private cloud computing environment - Abdullah, Rusli; Mahmoodian, Naghmeh (WSEAS, 2013)
Software Maintenance (SM) community of practice (CoP) is including the system maintainer as a service provider and the users as its service recipient. Based on this scenario, they are working together or work collaboratively in order to optimize the capabilities of the software, which we called it as SM as a service (SMaaS) process. In this context, The CoP can make use knowledge management system (KMS) as a tool in managing the SM knowledge as a best practice and lesson learnt. SM is the process of identifying and delivering the software as a product based on service level agreement (SLA) that has been made between service provider and the users. The paper will discuss the model on how the SM is offering its service of processes through knowledge life cycle which starting from knowledge acquisition, knowledge storing, knowledge dissemination, and knowledge application in order to avoid any shortcoming fault or failure especially during the software development (SD) in a private cloud computing environment. Therefore, by using the KMS model in managing knowledge of SM, CoP can utilize the SM knowledge in the KMS and it will reduces the mistake or errors, so that they can also maintain a good service besides in enhancing the return of investment (ROI) as well as the quality of software to the particular users.